GE_GERICHTE P/11007/2004 vom 26. September 2007 - GE Cour de justice (2007)
; ABUS D'AUTORITÉ ; LOI SUR LA POLICE ; FOUILLE ; PROPORTIONNALITÉ ; CANNABIS ; INDEMNITÉ ÉQUITABLE | CPP.198; CPP.114B.4; CPP.379; CP.312; LPOL.20.3